Organização e funcionamento dos comitês de ética em pesquisa do município de Belo Horizonte, Minas Gerais - Pollyana Anicio Magalh?es (2013)
INTRODUCTION: According to Resolution 196/96 of the Brazilian National Health Council, an Institutional Review Board (IRB) has the aim of protect research subjects thus keeping their safety. For its operation as described in the Brazilian resolutions and complementary, minimum pre-establish requirements must be archived. However there is scarcity of information about the profiles of these organs in the Brazilian scenario whose knowledge is essential to their improvement. OBJECTIVE: Analyze the organization and functioning of IRBs of the city of Belo Horizonte. Were considered only the IRBs registered in the National System of Research in Ethics, and with regular status in the National Research in Ethics Council. METHODS: Sectional and descriptive study, conducted with coordinators / deputy coordinators of 23 IRBs in the city of Belo Horizonte in the year 2012. Issues related to infrastructure, composition, process of installation and operation of the IRBs were investigated through a questionnaire. The results were analyzed using descriptive statistics. RESULTS: All the IRBs evaluated were founded between 1996 and 2006, 100% has bylaws and minutes of meetings and 52.2% of the interviewed reported needing some support staff. The vast majority of the member is composed of medical doctors, 100% have community members in the collegiate and 52.2% offered a course on ethics and bioethics; and 78.3% of the IRBs have their own physical space and an exclusive computer, with internet access. .DISCUSSION: Most boards have dedicated themselves to play their role, showing characteristics that are in agreement to the Brazilian resolutions. However, no IRB is exempt improvements, mostly related to the institutional support. CONCLUSION: The organization and operation of the IRBs of the city of Belo Horizonte have important points of improvement in order to perform its function with excellence. Beyond the analysis of the facts, works that have direct impact in the work done by the IRBs are extremely conciliated.